Chemical analysis method for co-oxidizing and complexing niobium in niobium alloy by adopting nitrososulfuric acid
By using a mixture of nitrososulfuric acid and nitric acid to dissolve niobium alloys, combined with tannic acid washing and high-temperature ashing, the uncertainties and errors in niobium alloy analysis in traditional methods have been resolved, achieving efficient and accurate niobium alloy analysis.
Patent Information
- Application Number
- CN202511141440.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-14
AI Technical Summary
Traditional methods for analyzing niobium alloys suffer from significant uncertainties, residual losses, and random errors due to the hydrofluoric acid dissolution process, and the analytical steps are cumbersome, resulting in unstable results.
Nitrosulphic acid is used instead of hydrofluoric acid, and a mixture of nitric acid and sulfuric acid is used to dissolve the niobium alloy. Then, tannic acid is used for washing and high-temperature ashing to eliminate complexing agent residues and improve dissolution efficiency and accuracy.
The analysis process is shortened, random errors are reduced, the accuracy of the results is improved by 8 to 35 times, the stability is improved by 5.1 to 15.8 times, and the reliability of the method is significantly enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention pertains to chemical analysis techniques, specifically a chemical analysis and testing method for niobium dissolution in nickel-niobium alloys. Background Technology
[0002] Niobium is a silvery-gray, relatively soft, and ductile rare high-melting-point metal. Its density is 8.57 g / cm³. 3 Niobium has a melting point of 2477℃ and a boiling point of 4744℃. At room temperature, niobium does not react with air and is not completely oxidized even when heated red-hot in oxygen. At high temperatures, niobium can directly combine with sulfur, nitrogen, and carbon. Niobium does not react with inorganic acids or alkalis and is insoluble in aqua regia, but it is soluble in hydrofluoric acid. The abundance of niobium in the Earth's crust is 20 ppm, and its resources are relatively concentrated. Due to its excellent superconductivity, high melting point, corrosion resistance, and wear resistance, niobium is widely used in steel, superconducting materials, aerospace, and nuclear energy.
[0003] Niobium alloys are highly promising high-temperature materials, exhibiting excellent high-temperature strength and good low-temperature plasticity. Furthermore, niobium possesses a small thermal neutron absorption cross-section, resistance to liquid metal corrosion, and good superconductivity (e.g., in Nb3Sn intermetallic compounds, palladium-niobium alloys, and niobium-titanium alloys), among other superior properties, making niobium alloys considered one of the most promising high-temperature materials.
[0004] Based on the fundamental chemical properties of niobium and a review of relevant documents, hydrofluoric acid is a good solvent for niobium. However, this places more stringent requirements on the reaction vessel compared to other common chemical reactions. In traditional analytical chemistry methods for niobium, high-content niobium is typically detected using gravimetric methods. Because the PTFE beakers used for hydrofluoric acid are opaque and not heat-resistant, it is difficult to easily observe the chemical reactions during the experiment. After the niobium alloy is dissolved, it must be transferred to a glass beaker for further experiments. Due to the insolubility of niobium compounds in dilute acids and water, uncertain residual losses are inevitable during the transfer process. Furthermore, traditional analytical methods cannot completely remove the complexing agent from the sample solution during sample processing, leading to incomplete precipitation of niobium compounds and a significant increase in the loss of niobium compounds in the final filtrate. This is one of the reasons why traditional methods result in unstable analytical results and large random errors. Additionally, the increased analytical steps reduce timeliness.
[0005] Given the limitations of traditional analytical methods in the dissolution process of niobium alloys, there is an urgent need to develop a new chemical analysis method for niobium elements in niobium alloys that is timely, has low error, and is highly accurate. Summary of the Invention
[0006] Since the main drawback of traditional analytical methods lies in the niobium alloy dissolution process, the authors of this invention have creatively proposed abandoning hydrofluoric acid in the niobium alloy dissolution process and selecting an inorganic solvent that has a more efficient dissolution effect on niobium and is more compatible with experimental containers. This shortens the experimental procedure, improves timeliness, and eliminates the random errors inherent in traditional analytical methods, thereby improving the accuracy of the results. Extensive experimental results show that the method of this invention is stable, reliable, and accurate in application.
[0007] To solve the above-mentioned technical problems, this invention proposes a chemical analysis method for niobium in niobium alloys that discards hydrofluoric acid and uses nitrososulfuric acid in a synergistic oxidation process.
[0008] A method for determining niobium in a niobium alloy, comprising the following steps:
[0009] (1) Weigh the niobium alloy sample, add nitric acid and sulfuric acid mixture, heat to dissolve until the sample is completely decomposed, evaporate to wet salt form, pour distilled water along the cup wall, continue heating until sulfuric acid fumes are exhausted, remove and cool;
[0010] The nitric acid-sulfur mixture in step (1) is a mixture of nitric acid and sulfuric acid; preferably, the volume ratio of nitric acid to sulfuric acid is Vnitric acid:V sulfuric acid = 1:1.
[0011] The mass of the niobium alloy sample in step (1) is 0.2000–0.5000 g;
[0012] The amount of nitrate-sulfuric acid used in step (1) is 40-25 mL, preferably 35-25 mL, and more preferably 30 mL;
[0013] The amount of distilled water used in step (1) is less than 30 mL or less than 20 mL, more preferably less than 10 mL, for example 15 mL, 12 mL, 10 mL, 9 mL, 8 mL, 7 mL, 6 mL, 5 mL, 4 mL, 3 mL, 2 mL, 1 mL;
[0014] In step (1), the concentration of nitric acid is concentrated nitric acid; preferably, the mass fraction of the concentrated nitric acid is 65% to 68%; more preferably, the density of the nitric acid is ρ = 1.84 g / cm³. 3 ;
[0015] In step (1), the sulfuric acid is concentrated sulfuric acid; preferably, the mass fraction of the concentrated sulfuric acid is 70% to 98.3%; more preferably, the density of the sulfuric acid is ρ = 1.42 g / cm³. 3 ;
[0016] The heating temperature in step (1) is 200-300℃;
[0017] (2) Add concentrated hydrochloric acid and heat at low temperature until the salt obtained in step (1) is completely dissolved and the solution is clear;
[0018] The mass fraction of the concentrated hydrochloric acid in step (2) is 36%–38%; the density of the concentrated hydrochloric acid is ρ = 1.19 g / cm³. 3 ;
[0019] The temperature for low-temperature heating in step (2) is 150–200°C;
[0020] (3) Remove the beaker, add 5g of filter paper pulp, add water to 200mL, heat to boiling for 3min; while stirring, add 100mL of tannic acid solution, continue heating to boiling for 10min, stop heating, and let stand;
[0021] The mass fraction of the tannic acid solution in step (3) is 1.8% to 2.2%; preferably 2%.
[0022] More preferably, the method for preparing the tannic acid solution in step (3) is as follows: 2 grams of tannic acid are heated and dissolved in 100 mL of distilled water;
[0023] (4) Filter with quantitative filter paper, wash the beaker 3-5 times with tannic acid washing solution, wash the precipitate 3-5 times, retain the precipitate and discard the filtrate;
[0024] The tannic acid washing solution in step (4) includes tannic acid and hydrochloric acid; wherein the mass fraction of tannic acid is 0.3% to 0.8% and the volume fraction of hydrochloric acid is 5% to 7%;
[0025] Preferably, the preparation method of the tannic acid washing solution in step (3) is as follows: 0.5 g of tannic acid is heated and dissolved in 100 mL of distilled water, and 6 mL of hydrochloric acid is added;
[0026] (5) Transfer the precipitate and filter paper to a platinum crucible that has been weighed at 950°C and heat it to ashed. After ashing, place the sample crucible in a muffle furnace and heat it to 950°C. Maintain the high temperature for 30-60 minutes for carbonization. After the crucible has reached constant weight, calculate the niobium content.
[0027] Preferably, the present invention provides an embodiment: a method for determining niobium in a niobium alloy, comprising the following steps:
[0028] (1) Accurately weigh 0.2000-0.5000g of niobium alloy sample into a 400mL dry beaker, add 30mL of nitric acid-sulfur mixture, cover with a watch glass, heat to dissolve until the sample is completely decomposed, evaporate to a wet salt state, rinse a small amount of water along the beaker wall, preferably within 30mL or 20mL, more preferably within 10mL, for example 15mL, 12mL, 10mL, 9mL, 8mL, 7mL, 6mL, 5mL, 4mL, 3mL, 2mL, 1mL, continue heating until the sulfuric acid fumes are exhausted, remove and cool, rinse the watch glass;
[0029] In step 1), the nitric acid-sulfuric acid mixture is a mixture of nitric acid and sulfuric acid; preferably, the volume ratio of nitric acid to sulfuric acid is Vnitric acid:V sulfuric acid = 1:1.
[0030] (2) Add concentrated hydrochloric acid and heat at low temperature until the salt in the beaker is completely dissolved and the solution is clear;
[0031] (3) Remove the beaker, add 5g of filter paper pulp, add water to 200mL, and heat to a boil; while stirring, add 100mL of tannic acid solution to the sample beaker, continue heating to a boil for 10min, stop heating, let the sample solution stand overnight, and keep the total volume of the solution at 300mL.
[0032] (4) Filter the sample solution with quantitative filter paper, wipe the precipitate attached to the cup wall and glass rod with filter paper and put it into the precipitate in the funnel, wash the beaker 3 to 5 times with tannic acid washing solution, wash the precipitate 3 to 5 times, retain the precipitate and discard the filtrate.
[0033] (5) Transfer the precipitate and filter paper to a constant-weight platinum crucible, place it on a hot plate for heating and ashing. After ashing, place the sample crucible in a muffle furnace for high-temperature carbonization. After the crucible reaches a constant weight, calculate the results.
[0034] All reagents used in the above schemes were of analytical grade.
[0035] Reagent: Sulfuric acid (ρ = 1.84 g / cm³) 3 ).
[0036] Nitric acid (ρ = 1.42 g / cm³) 3 ).
[0037] Hydrochloric acid (ρ = 1.19 g / cm³) 3 ).
[0038] Tannic acid solution (2%): Weigh 2 grams of tannic acid and heat to dissolve in 100 mL of distilled water.
[0039] Tannic acid washing solution: Weigh 0.5 g of tannic acid, heat and dissolve it in 100 mL of distilled water, then add 6 mL of hydrochloric acid.
[0040] The beneficial effects of this invention are at least as follows:
[0041] 1. Using nitrososulfuric acid instead of hydrofluoric acid to dissolve niobium in niobium alloys shortens the analysis process, improves analysis efficiency, avoids random errors generated during the transfer from PTFE beakers to glass beakers, and improves the accuracy of results, which is 8 to 35 times that of existing technologies.
[0042] 2. Eliminates the residue of complexing agent, eradicates the hidden danger of a large amount of niobium compound leaking into the filtrate of analytical step (4), and improves the reliability and stability of the method. The stability is 5.1 to 15.8 times that of the prior art. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0044] All chemical reagents used in the experimental methods employed in this invention are analytical grade reagents.
[0045] Synthetic standard (I): 16.83% niobium + 83.17% nickel; Synthetic standard (II): 52.47% niobium + 47.53% nickel; Synthetic standard (III): 75.18% niobium + 24.82% nickel (all metals used in the synthetic standards are high-purity niobium and high-purity nickel). These are hereinafter referred to as standard (I), standard (II), and standard (III).
[0046] The solvents used in the following examples are as follows:
[0047] Sulfuric acid (ρ = 1.84 g / cm³) 3 ).
[0048] Nitric acid (ρ = 1.42 g / cm³) 3 ).
[0049] Hydrochloric acid (ρ = 1.19 g / cm³) 3 ).
[0050] Tannic acid solution (2%): Weigh 2 grams of tannic acid and heat to dissolve in 100 mL of distilled water.
[0051] Tannic acid washing solution: Weigh 0.5 g of tannic acid, heat and dissolve it in 100 mL of distilled water, then add 6 mL of hydrochloric acid.
[0052] Example 1
[0053] (1) Accurately weigh 0.2000~0.5000g of niobium alloy sample into a 400mL dry beaker, add 30mL of pre-prepared nitric acid-sulfuric acid mixture (V concentrated nitric acid: V concentrated sulfuric acid = 1:1), cover with a watch glass, heat to dissolve until the sample is completely decomposed, evaporate to a wet salt state, rinse a small amount of water along the beaker wall, continue heating until the sulfuric acid fumes are exhausted, remove and cool, and rinse the watch glass.
[0054] (2) Add 20 mL of concentrated hydrochloric acid and heat at low temperature until the salt in the beaker is completely dissolved and the solution is clear.
[0055] (3) Remove the beaker, add filter paper pulp, add water to 200 mL, and heat to boiling for 3 min. While stirring, add 100 mL of tannic acid solution to the sample beaker, continue heating to boiling for 10 min, stop heating, and let the sample solution stand overnight (maintain the total volume of the solution at 300 mL during this process).
[0056] (4) Filter the sample solution with quantitative filter paper. Wipe the precipitate attached to the cup wall and glass rod clean with filter paper and put it into the precipitate in the funnel. Wash the beaker 3 to 5 times with tannic acid washing solution and wash the precipitate 3 to 5 times. Keep the precipitate and discard the filtrate.
[0057] (5) Transfer the precipitate and filter paper to a platinum crucible that has been weighed at 950℃, place it on a hot plate for heating and ashing. After ashing, place the sample crucible in a muffle furnace and heat it to 950℃. Maintain the high temperature for 30-60 minutes for carbonization. Calculate the results after the crucible has reached constant weight.
[0058]
[0059] m0 represents the mass of the empty crucible after it has reached constant weight at 950℃, in grams;
[0060] m1 represents the sample mass, in grams;
[0061] m2 represents the mass of niobium pentoxide and the crucible after being brought to constant weight at 950℃, in grams.
[0062] Table 1 Precision and accuracy of nickel-niobium alloy and standard samples in Example 1
[0063]
[0064] Example 2
[0065] (1) Accurately weigh 0.2000~0.5000g of niobium alloy sample into a 400mL dry beaker, add 30mL of pre-prepared nitric acid-sulfuric acid mixture (V concentrated nitric acid: V concentrated sulfuric acid = 1:1), cover with a watch glass, heat to dissolve until the sample is completely decomposed, evaporate to a wet salt state, rinse a small amount of water along the beaker wall, continue heating until the sulfuric acid fumes are exhausted, remove and cool, and rinse the watch glass.
[0066] (2) Add 20 mL of concentrated hydrochloric acid and heat at low temperature until the salt in the beaker is completely dissolved and the solution is clear.
[0067] (3) Remove the beaker, add filter paper pulp, add water to 200 mL, and heat to boiling for 3 min. While stirring, add 100 mL of tannic acid solution to the sample beaker, continue heating to boiling for 10 min, stop heating, and let the sample solution stand overnight (maintain the total volume of the solution at 300 mL during this process).
[0068] (4) Filter the sample solution with quantitative filter paper. Wipe the precipitate attached to the cup wall and glass rod clean with filter paper and put it into the precipitate in the funnel. Wash the beaker 3 to 5 times with tannic acid washing solution and wash the precipitate 3 to 5 times. Keep the precipitate and discard the filtrate.
[0069] (5) Transfer the precipitate and filter paper to a platinum crucible that has been weighed at 950℃, place it on a hot plate for heating and ashing. After ashing, place the sample crucible in a muffle furnace and heat it to 950℃. Maintain the high temperature for 30-60 minutes for carbonization. Calculate the results after the crucible has reached constant weight.
[0070] Table 2 Precision and accuracy of nickel-niobium alloy and standard samples in Example 2
[0071]
[0072] Example 3
[0073] (1) Accurately weigh 0.2000~0.5000g of niobium alloy sample into a 400mL dry beaker, add 30mL of pre-prepared nitric acid-sulfuric acid mixture (V concentrated nitric acid: V concentrated sulfuric acid = 1:1), cover with a watch glass, heat to dissolve until the sample is completely decomposed, evaporate to a wet salt state, rinse a small amount of water along the beaker wall, continue heating until the sulfuric acid fumes are exhausted, remove and cool, and rinse the watch glass.
[0074] (2) Add 20 mL of concentrated hydrochloric acid and heat at low temperature until the salt in the beaker is completely dissolved and the solution is clear.
[0075] (3) Remove the beaker, add filter paper pulp, add water to 200 mL, and heat to boiling for 3 min. While stirring, add 100 mL of tannic acid solution to the sample beaker, continue heating to boiling for 10 min, stop heating, and let the sample solution stand overnight (maintain the total volume of the solution at 300 mL during this process).
[0076] (4) Filter the sample solution with quantitative filter paper. Wipe the precipitate attached to the cup wall and glass rod clean with filter paper and put it into the precipitate in the funnel. Wash the beaker 3 to 5 times with tannic acid washing solution and wash the precipitate 3 to 5 times. Keep the precipitate and discard the filtrate.
[0077] (5) Transfer the precipitate and filter paper to a platinum crucible that has been weighed at 950℃, place it on a hot plate for heating and ashing. After ashing, place the sample crucible in a muffle furnace and heat it to 950℃. Maintain the high temperature for 30-60 minutes for carbonization. Calculate the results after the crucible has reached constant weight.
[0078] Table 3 Precision and accuracy of ferroniobium alloy and standard samples in Example 3
[0079]
[0080] Comparative Example 1
[0081] Most existing publicly available methods employ a process of dissolving niobium alloys with hydrofluoric acid, followed by using sulfuric acid to generate appropriate fumes and drive away the hydrofluoric acid. This method was validated using the aforementioned standard samples, and the results are shown in Table 4.
[0082] Table 4. Precision and Accuracy of Comparison Results
[0083]
[0084] Table 5 Comparison of accuracy results between this application and the comparative example.
[0085]
[0086]
[0087] Based on a comprehensive analysis of the results in Tables 1-5, comparing the accuracy and precision of the detection results, the method of this invention is superior to the method using hydrofluoric acid to dissolve niobium alloy and sulfuric acid to appropriately fume and drive away the hydrofluoric acid. The precision of the method described in the embodiments of this invention is 5.1 to 15.8 times that of the existing method in Comparative Example 1 (i.e., the dissolution mode using hydrofluoric acid + sulfuric acid); in terms of accuracy, the deviation value of the comparative example is as high as 8 to 35 times that of the embodiments.
[0088] Comparative Example 2
[0089] The ratio and volume of the nitrate-sulfur mixed acid were verified using samples 1, 2, and 3, and the results are shown in Table 5.
[0090] Table 6 Comparison of Sample Dissolution Experiment Results
[0091]
[0092]
[0093] Based on the experimental results in Table 6, the optimal ratio of nitric acid to sulfuric acid is 1:1, with an added volume of 30 mL.
[0094] This invention provides an efficient, reliable, and accurate analytical method for high-niobium content niobium alloys. The invention uses nitrososulfuric acid instead of hydrofluoric acid to dissolve the niobium alloy sample. After dissolution, nitrososulfuric acid is thoroughly used to remove the niobium, based on its fundamental chemical properties, to prevent it from having a negative complexing effect on the subsequent niobium compound precipitation process using tannin. The subsequent hydrochloric acid solution dissolution and clarification step fully releases other alloying elements trapped within the niobium insoluble compounds, which are then complexed by chloride ions and retained in the supernatant. This eliminates random errors caused by inclusions during precipitation and improves the purity of niobium pentoxide. This invention uses nitrososulfuric acid, an ideal solvent for niobium with both oxidizing and complexing properties, instead of traditional hydrofluoric acid. This improves the friendliness of the reaction process to the container, eliminates random errors caused by container transfer, residues adhering to the vessel walls, and inclusions of other alloying elements in niobium precipitation compared to traditional methods, thus improving the accuracy and reliability of the results; shortening the experimental procedure and improving the timeliness of the method; and thoroughly removing the complexing agent, significantly reducing niobium leakage residue in the filtrate during tannin precipitation, thereby improving the accuracy of the method. This invention has the advantages of being simple to operate, reliable, timely, and accurate.
Claims
1. A method for determining niobium in a niobium alloy, wherein, Includes the following steps: (1) Accurately weigh 0.2000~0.5000g of niobium alloy sample into a 400mL dry beaker, add 30mL of nitric acid-sulfur mixture, cover with a watch glass, heat to dissolve until the sample is completely decomposed, evaporate to a wet salt state, pour water along the beaker wall, continue heating until the sulfuric acid fumes are exhausted, remove and cool, and rinse the watch glass. In step 1), the nitric acid-sulfuric acid mixture is a mixture of nitric acid and sulfuric acid; preferably, the volume ratio of nitric acid to sulfuric acid is Vnitric acid:V sulfuric acid = 1:
1. (2) Add concentrated hydrochloric acid and heat at low temperature until the salt in the beaker is completely dissolved and the solution is clear; (3) Remove the beaker, add filter paper pulp, add water to 200mL, and heat to a boil; While stirring, add 100 mL of tannic acid solution to the sample beaker, continue heating to boiling for 10 min, stop heating, let the sample solution stand overnight, and keep the total volume of the solution at 300 mL. (4) Filter the sample solution with quantitative filter paper, wipe the precipitate attached to the cup wall and glass rod with filter paper and put it into the precipitate in the funnel, wash the beaker 3 to 5 times with tannic acid washing solution, wash the precipitate 3 to 5 times, retain the precipitate and discard the filtrate. (5) Transfer the precipitate and filter paper to a constant-weight platinum crucible, place it on a hot plate for heating and ashing. After ashing, place the sample crucible in a muffle furnace for high-temperature carbonization. After the crucible reaches a constant weight, calculate the results.
2. The method for determining niobium in a niobium alloy according to claim 1, wherein, In step (1), the concentration of nitric acid is concentrated nitric acid; preferably, the mass fraction of the concentrated nitric acid is 65% to 68%; more preferably, the density of the nitric acid is ρ = 1.84 g / cm³. 3 .
3. The method for determining niobium in a niobium alloy according to claim 1, wherein, In step (1), the sulfuric acid is concentrated sulfuric acid; preferably, the mass fraction of the concentrated sulfuric acid is 70% to 98.3%; more preferably, the density of the sulfuric acid is ρ = 1.42 g / cm³. 3 .
4. The method for determining niobium in a niobium alloy according to claim 1, wherein, The mass fraction of the concentrated hydrochloric acid in step (2) is 36%–38%; the density of the concentrated hydrochloric acid is ρ = 1.19 g / cm³. 3 ; Preferably, the amount of concentrated hydrochloric acid used is 20 mL.
5. The method for determining niobium in a niobium alloy according to claim 1, wherein, The mass fraction of the tannic acid solution in step (3) is 1.8% to 2.2%; preferably 2%. More preferably, the method for preparing the tannic acid solution in step (3) is as follows: 2 grams of tannic acid are heated and dissolved in 100 mL of distilled water.
6. The method for determining niobium in a niobium alloy according to claim 1, wherein, The tannic acid washing solution in step (4) includes tannic acid and hydrochloric acid; wherein the mass fraction of tannic acid is 0.3% to 0.8% and the volume fraction of hydrochloric acid is 5% to 7%; Preferably, the preparation method of the tannic acid washing solution in step (3) is as follows: 0.5 g of tannic acid is heated and dissolved in 100 mL of distilled water, and 6 mL of hydrochloric acid is added.
7. The method for determining niobium in a niobium alloy according to claim 1, wherein, The heating temperature in step (1) is 200-300℃.
8. The method for determining niobium in a niobium alloy according to claim 1, wherein, The temperature for low-temperature heating in step (2) is 150-200℃.
9. The method for determining niobium in a niobium alloy according to claim 1, wherein, In step (3), the amount of filter paper pulp used is 5g.
10. The method for determining niobium in a niobium alloy according to claim 1, wherein, The temperature for heating and ashing in step (5) is 300-500℃; preferably, the temperature for high-temperature carbonization is 900-1000℃.